Comportamento de fungicida em plantas de soja submetidas a diferentes regimes hídricos e horários de aplicação - Stefanello, Marlon Tagliapietra (2014)
The climatic factors, especially water deficit, cause changes in biochemical and morphophysiological aspects in soybean plants, which consequently affect the performance of fungicide applications on leaves and pathogenicity of fungi. This study aimed to evaluate the performance of fungicide in soybean under different water regimes and times of application. For this purpose two experiments were conducted, one in the greenhouse and one on the field, both in Itaara RS, Brazil. The experimental design in greenhouse was composed by completely randomized design with four replications in a factorial (2x6x5), which factors were composed, factor 01: two water regimes (50-60% of the field capacity and 90-100% of the field capacity); factor 02: five times of application (04:00 a.m., 09:00 a.m., 14:00 p.m., 18:00 p.m., 23:00 p.m.) and a control without fungicide applying; factor 03: four time periods between the fungicide application and simulated rain (0, 30, 60 and 120 ) plus a control with no rain. Fungicide comprising the active ingredients Trifloxystrobin + Prothioconazole (70.0 + 60.0 g ha-1 a.i.) was used with the addition of Aureo® at a dose of 0.375 l ha-1 c.p. The parameters evaluated were the number of days until the first pustule preview of asian rust, the severity of Phakopsora pachyrhizi and Cercospora kikuchii in leaves, incidence of C. kikuchii in grain, relative chlorophyll content, stomatal density, trichome density, concentration of hydrogen peroxide, lipid peroxidation, yield and grain weight. The experimental design in the field was composed by randomized blocks with split plots. The experiment consisted of two factors (6x5). The first factor was composed of the application time (04:00 a.m., 09:00 a.m., 14:00 p.m., 18:00 p.m., 23:00 p.m.) and a control without fungicide applying. The second factor was composed of the time periods between the fungicide application and simulated rain (0, 30, 60 and 120 ) plus a control with no rain. The parameters evaluated were the severity of the asian rust, the relative chlorophyll content stratified in three thirds of the canopy, area under the disease progress curve, yield and hundred grain weight. The results indicate that the penetration of fungicide is faster in leaflets in sunlight. It finds that the application of fungicides in plants under water deficit provides the greatest number of days until the first pustule preview. The simulated rainfall has a greater effect on the removal of fungicide applications made at night. The fungicide application in leaflets made at 09:00 am provides the greatest number of days until the first pustule preview. Soybean plants in water deficit develop strategies to reduce the loss of water, which affects the pathogenicity of Phakopsora pachyrhizi and Cercospora kikuchii.